Business ethics and business education: A report from a regional state university - Castro, Barry (Journal of business ethics, 1989)
My central point is that the recent wave of interest in business ethics is an opportunity to review the whole enterprise of undergraduate business education. Business ethics, taught as if the students, faculty, curriculum and organization of the business school were important parts of the subject matter, is a way both to affirm the seriousness of ethical inquiry and to build an increased sense of collegial responsibility for the overall curriculum students are asked to undertake.